Mechanisms of Tubulin Binding Ligands to Target Cancer Cells: Updates on their Therapeutic Potential and Clinical Trials - Kumar, Bhupinder; Kumar, Rakesh; Skvortsova, Ira; Kumar, Vinod (Current Cancer Drug Targets, 2017)
Background: A number of chemically diverse substances bind to the tubulin and inhibit cell proliferation by disrupting microtubule dynamics. There are four binding sites for the ligands binding to the tubulin; taxane/epothilone and laulimalide/peloruside binding ligands stabilize microtubule while vinca and colchicine binding site agents promote microtubule depolymerization. Most of the tubulin binding ligands disturb the tubulin-microtubule dynamic equilibrium but these may exhibit anticancer activities through different mechanisms. Taxanes and epothilones are widely used cytotoxic agents and are found effective against different types of human malignancies. However, taxanes are susceptible to pgp mediated multi-drug resistance, dose limiting hematopoietic toxicity and cumulative neurotoxicity. Vinca alkaloids are already in clinical practice, but ligands binding to the colchicine site are still in the different stages of clinical trials. Objective: In the current review article, plausible mechanistic details about the interactions of ligands at the binding pocket and subsequent changes in the tubulin structure are described. The review article also illustrated different formulations of the tubulin binding agents in combination with other chemotherapeutic agents and their therapeutic potential against various human malignancies. Conclusion: Tubulin targeting agents emerged as one of the most successful anticancer drugs and a number of structurally different chemical compounds are in advance stages of clinical development.
Keywords: combination therapy